2013
DOI: 10.3382/ps.2012-02572
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective effect of sea buckthorn (Hippophae rhamnoides) berries on induced aflatoxin B1 poisoning in chickens

Abstract: The leaves and berries of sea buckthorn (SB; Hippophae rhamnoides; family Elaeagnaceae) are medically claimed as having phytoantioxidant, antiinflammatory, and anticancerous properties in humans. This study evaluated the hepatoprotective activity of oil from SB berries against toxicity induced by aflatoxin B1 (AFB1) in broiler chickens. The toxicity of AFB1 led to lower total serum proteins and specifically reduced albumin (P < 0.001). Serum aspartate aminotransferase increased from 191.14 ± 11.56 to 218.80 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…These results are in agreement with previous research, which showed that the intake of AFB could induce the decrease of the relative weight of thymus and BF in broilers (Santin et al, 2003;Manafi et al, 2012). The increase of splenic relative weight observed in our study was also in line with earlier findings (Rosa et al, 2001;Solcan et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…These results are in agreement with previous research, which showed that the intake of AFB could induce the decrease of the relative weight of thymus and BF in broilers (Santin et al, 2003;Manafi et al, 2012). The increase of splenic relative weight observed in our study was also in line with earlier findings (Rosa et al, 2001;Solcan et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…In the present study, the relative weight of spleen was used to judge the extent of spleen lesions. The relative weight of the spleen in birds fed with corn naturally contaminated with AFB 1 and AFB 2 increased, which was similar to the results from other researchers [20,21,22]. According to histopathological observation, the relative weight increase seems to be due to the congestion of red pulp in the spleen.…”
Section: Discussionsupporting
confidence: 89%
“…In Indian, Chinese and Tibetan medicines sea-buckthorn fruits were added to medicines, as their ingredients were thought to have a beneficial effect on the function of the alimentary, respiratory and circulatory systems. Nowadays, many studies confirm the practices of Asian doctors from hundreds of years ago [41–44]. Physical and chemical properties of sea-buckthorn seed oil are contained in Table 1.…”
Section: Botanical Description Of the Productmentioning
confidence: 96%